Contratualização de resultados e desempenho no setor público: a experiência do contrato programa nos hospitais da administração direta no Estado de São Paulo - Perdicaris, Priscilla Reinisch (2012)
The aim of this research is to evaluate the impact of results-based contracting on the performance of public managed and owned hospitals within the state of São Paulo. It intends to fulfill a gap in studies on New Public Management, showing correlations between the implementation of management polices and the results (outputs and outcomes) of an organization. The hypotheses to be tested is that management contracts increases performance by improving coordination within the government’s strategic centre, and stimulating organizational learning, while it promotes the adequate incentives to continuous improvement. A secondary objective of the research will be to understand how contracts are designed and managed, in order to minimize the problems of principal-agent relationship arising from this type of practice. The literature indicates that one way to minimize such problems has been the use of contracts based on trust, reciprocity and mutual learning, the socalled relational contracts, which will be explored in the case study analysis. The case selected to test the hypothesis is that of performance contracts of state managed hospital units from with the Health Department of São Paulo State (Secretaria Estadual de Saúde de São Paulo – SES/SP), through the “Program Contract”, which started at the end of 2008. This experience will be used to test the contribution of results-based contracting to the quality of hospital services. Results show that there is a correlation between the introduction of contracts and hospital performance, with better outcomes in almost all of the aspects analyzed.